Potential of Seed Powder (Tamarindus indica L.) on Cholesterol Levels: Potensi Seduhan Serbuk Biji Asam Jawa (Tamarindus indica) Terhadap Kadar Kolesterol - Purwaningsih, Nur Vita; Widyastuti, Rahma; Maulidiyanti, Ellies Tunjung Sari; Saputro, Tri Ade; Rohmayani, Vella; Ainutajriani, Ainutajriani (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
ABSTRACT Coronary heart disease (CHD) is the leading cause of death after stroke in all age groups at 12.9%. The main reason is the amount of cholesterol in the blood. Tamarind (Tamarindus indica) is a traditional herb that has the potential to lower cholesterol, because it contains flavonoids, saponins, foliphenols, pectin, organic acids, vitamin B and vitamin C that can lower cholesterol. The purpose of this study was to determine the effect of tamarind seed powder (Tamarindus indica) on cholesterol levels. This type of research is experimental with pre-test and post-test with control group research design. The population and sample of this study were a group of mice totaling 32 mice. The location of this research was conducted at the Animal Husbandry Center (PUSVETMA). Data collection procedures were carried out by examining the cholesterol levels of mice before and after treatment. The data obtained were followed up with normality test and independent t test. The results of the study using the unpaired t test gave the result of p=0.000 (p<0.05). The conclusion of this study is that there is an effect of seed powder (Tamarindus indica) on cholesterol levels. Keyword : Seeds Tamarindus indica L., cholesterol levels, Mice (Mus musculus)